Ovarian aging: pathophysiology and recent developments in maintaining ovarian reserve - Hirano, Mana; Onodera, Takako; Takasaki, Kazuki; Takahashi, Yuko; Ichinose, Takayuki; Nishida, Haruka; Hiraike, Haruko; Nagasaka, Kazunori (Frontiers in Endocrinology, 2025)
According to the World Health Organization, infertility has emerged as a critical public health issue, affecting approximately 48 million couples and 186 million individuals worldwide. Ovarian aging—defined by the progressive depletion and functional deterioration of the primordial follicle pool—accounts for a major proportion of female−factor infertility and has profound socioeconomic consequences. It is characterized by a decline in follicle quantity and quality, which significantly influences infertility. This phenomenon is multifaceted, involving genetic predisposition, hormonal fluctuations, mitochondrial dysfunction, oxidative stress, and ovarian microenvironment alterations. This review explores the biological mechanisms of ovarian aging, evaluates current therapeutic advances, and identifies strategies to maintain ovarian function and prolong reproductive lifespan. Recent advancements—including antioxidant and mitochondria-targeted therapies, hormonal modulation, growth factor interventions (e.g., platelet-rich plasma), mitochondrial transfer, and in vitro follicle activation—show promise for maintaining ovarian reserve. Fertility preservation strategies, such as ovarian tissue cryopreservation and transplantation, and pharmacological inhibition of follicle depletion, have expanded therapeutic options. The development of personalized treatments, refined biomarkers, and integrative strategies combining antioxidants, hormonal therapies, and novel fertility preservation techniques is essential. Therefore, translational research utilizing animal models remains crucial for validating efficacy and safety prior to clinical application. Future research should prioritize validating these emerging therapies through larger clinical trials to ensure safe, effective, and practical translation into clinical practice, ultimately prolonging reproductive lifespan and enhancing quality of life for aging women.